Gröna tak som en metod för dagvattenhantering i Norrbotten - Rydlinge, Olov; Widetun, Jenny (2014)
The high percentage of impervious surfaces in urban environment contributes to increased load on the stormwater system during heavy rains and large amounts of snowmelt. To reduce the load and prevent flooding in urban communities, green infrastructure could be introduced, such as green roofs (vegetated roofs). Green roofs performance in cold temperature is not widely studied, which contributed to the purpose of the thesis in relation of the investigation of a green roof located in central Luleå. Through a flow meter at the outlet runoff from the green roof and an estimated flow from a metal roof next to the green roof could the accumulated runoff volumes be calculated and compared between the two roofs. The estimated flow from the metal roof was calculated with the roof area and rainfall data from Luleå Airport. To examine the quality of runoff water samples were taken from the two roofs runoff. The samples were analyzed for metals, nitrogen and phosphorus content at ALS and pH were measured. By constructing a computer model of the area where the sampling occurred, has an appreciation of how a common Swedish inner city neighborhoods reduces runoff by installing various percentages of green roofs. This with the help of the software "Storm Water Management Model 5.1005", where the construction of the model was carried through by visual estimation at the sight, as well as pre-existing mappings and models. The result showed that the green roof had a delaying effect on runoff for all 6 occasions of rain and a high retention capacity in which the average of the projected percentage retention factors was approximately 92 %. Runoff from the green roof contained high concentrations of the nutrients N and P, while the metal concentrations were usually lower compared to the runoff from the metal roof. When comparing the different water volumes were accumulated masses of the selected metals, Cd, Cu, Pb and Zn, lower in runoff from the green roof. The extremely high concentrations of Zn in runoff from the metal roof are due ...